2022
DOI: 10.3389/fitd.2022.982421
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the macrofilaricidal efficacy of oxfendazole and its isomers against the rodent filaria Litomosoides sigmodontis

Abstract: Oxfendazole is one of the lead macrofilaricidal candidates for the treatment of onchocerciasis and lymphatic filariasis. Originally, oxfendazole was developed for the veterinary market, where it is mainly used to treat intestinal helminth infections. In humans, oxfendazole was proven to be safe in multiple ascending dose studies. Furthermore, previous experimental studies demonstrated that the benzimidazoles class is active in animals and humans against filarial nematodes. In the present study, we have compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Similarly, oxfendazole is a drug that is used against intestinal helminths in the veterinary field over several decades. In vitro and in vivo animal studies showed that oxfendazole is also active against filarial nematodes [31][32][33]. Oxfendazole was tested in Phase 1 clinical trials [34] and will be tested in onchocerciasis, loiasis, mansonellosis and Trichuris trichiura patients in a Phase 2 clinical basket trial [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, oxfendazole is a drug that is used against intestinal helminths in the veterinary field over several decades. In vitro and in vivo animal studies showed that oxfendazole is also active against filarial nematodes [31][32][33]. Oxfendazole was tested in Phase 1 clinical trials [34] and will be tested in onchocerciasis, loiasis, mansonellosis and Trichuris trichiura patients in a Phase 2 clinical basket trial [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical studies in Mexico demonstrated that flubendazole has high macrofilaricidal activity [38,39] and in vivo laboratory studies confirmed this activity [40]. Recently, the important role of the immune system in supporting the macrofilaricidal efficacy for the related drug oxfendazole was demonstrated in the Litomosoides sigmodontis filarial mouse model [33]. Despite the limitation that some candidates may require an intact immune system for efficacy, several promising candidates were identified.…”
Section: Discussionmentioning
confidence: 99%